A scoping review of supports on college and university campuses for autistic post-secondary students - Nelson, Hilary; Switalsky, Danielle; Ciesielski, Jill; Brown, Heather M.; Ryan, Jackie; Stothers, Margot; Coombs, Emily; Crerear, Alessandra; Devlin, Christina; Bendevis, Chris; Ksiazek, Tommias; Dwyer, Patrick; et al. (Frontiers in Education, 2023)
Given the demand to better address the principles of equity, diversity, inclusion, and accessibility in higher education, research into both barriers and promising practices to support autistic students on post-secondary campuses has advanced significantly in the last decade. The objective of this scoping review is to identify, map, and characterize literature that enumerates and describes supports for autistic post-secondary students. This scoping review was limited to peer-reviewed research published between January 2012 and May 2022, in these databases: Web of Science, PsycINFO, Medline, EMBASE, ERIC, Social Work Abstracts, Social Services Abstracts, and EMCARE. The review aligns to Joanna Briggs Institute methodology for scoping reviews and includes consultation with an expert panel made up of the Autistic Community Partners -four autistic individuals with postsecondary experience who acted as co-researchers.Literature on creating accessible campuses were mapped in three ways: 1) through the four domains of the PASS Taxonomy; 2) ten support categories characterizing types of supports, and 3) nine emergent themes, based on autistic experiences on support and campus navigation, were inductively and iteratively coded throughout process. This review summarizes both areas that have been researched and under-studied areas in the literature that act as contributors or challenges for autistic students on postsecondary campuses. It was also the first scoping review, to our knowledge, to integrate lived experience within the methods and results analysis to describe the current state of the evidence on post-secondary campuses. Mapping the literature in known and emerging categories indicated that broad categories of support are experienced variably by autistic students. Findings provide multiple avenues for future research.